2008
DOI: 10.1007/s10822-008-9212-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structures and properties of cyclic peptide nanotubes by experiment and molecular dynamics

Abstract: In order to investigate the structures and properties of cyclic peptide nanotubes of cyclo[(-D: -Phe-L: -Ala)( n = 3,4,5,6)-], cyclo[(-D: -Phe-L: -Ala)( n = 4)-] was synthesized and self-assembled to nanotubes, and its structure and morphology of the nanotube were characterized by mass spectrometry (MS), fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). On the basis of these experimental results, the structures of cyclo[(-D: -Phe-L: -Ala)( n = 3,4,5,6)-] were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…(29) Such a hydrogen bond network in our ortho -CPN was relatively persistent during the course of CMD simulation. Interestingly, the side chains of the eight intersubunit peptides rearranged their orientations and have led to the formation of a new hydrogen bond network in consecutive rings, particularly between l -Trp and l -Gln or between l -Gln and l -Gln.…”
Section: Resultsmentioning
confidence: 88%
“…(29) Such a hydrogen bond network in our ortho -CPN was relatively persistent during the course of CMD simulation. Interestingly, the side chains of the eight intersubunit peptides rearranged their orientations and have led to the formation of a new hydrogen bond network in consecutive rings, particularly between l -Trp and l -Gln or between l -Gln and l -Gln.…”
Section: Resultsmentioning
confidence: 88%
“…For the motion behaviour of water molecules in a cyclo[(-D-Phe-L-Ala) n¼4 À ] peptide nanotube, Zhu et al (2008) use a COMPASS force field to show that due to the stacking arrangement of antiparallel rings, water molecules do not diffuse unilaterally, but do so in one dimension. Song et al (2013) study the dynamics of Na þ transportation in a cyclic peptide nanotube of 8 Â(WL) 4 /POPE that contains water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…CPNs with inner diameter ranging from 5.9 to 13.1 Å can be readily achieved by selecting the number of amino acid subunits. [18] The fabrication of sub-nanometer porous membranes remains challenging using conventional techniques, [2] and therefore the design of a biological membrane using a polymerizable LLC system in conjunction with CPNs could potentially help to overcome current fabrication limitations. Recently, we showed that the nanostructured domains presented in LLC systems could be used to align CPNs in a similar manner to that of protein membranes in biological membrane.…”
Section: Doi: 101002/macp201800307mentioning
confidence: 99%